Acervos científicos digitais nas bibliotecas universitárias da UFRJ: competências, estratégias e normas para sua salvaguarda - Souza, Marcelle Lopes de (2017)
This dissertation is focused on the preservation of scientific digital collections which belong to the university libraries and information system (Sistema de Bibliotecas e Informação) of Rio de Janeiro’s Federal University (Universidade Federal do Rio de Janeiro) SIBI/UFRJ. The research provided consolidated data related to the university’s libraries which integrate the system, the use of electronic books in universities and digital preservation through the implementation of a policy focused on the PANTHEON repository of UFRJ. The methodology used was an exploratory and descriptive research that intended to identify possible actions, programs, norms and necessary competences related to the digital preservation in Brazil. We analysed some significant iniciatives such as: Rede Cariniana/IBICT; Iniciativa Legatum – a research project from Grupo de pesquisas CRIDI - Cultura, Representação e Informação Digitais; Câmara Técnica de Documentos Eletrônicos (CTDE), subordinated to the National Council of Archives (Conselho Nacional de Arquivos - CONARQ); PANTHEON / UFRJ Repository (Repositório PANTHEON / UFRJ) and reflecting on interdisciplinary relationships between archives and libraries. In the end we concluded that SIBI is taking part in actions to digitally preserve collections through the implementation of its institutional repository that enables the preservation of its scientific collections, according to norms and standards, both national and international which guarantee the accessibility, integrity, reliability and information propagation.